Unveiling the roles of Sertoli cells lineage differentiation in reproductive development and disorders: a review - Gao, Yang; Wang, Zican; Long, Yue; Yang, Lici; Jiang, Yongjian; Ding, Dongyu; Teng, Baojian; Chen, Min; Yuan, Jinxiang; Gao, Fei (Frontiers in Endocrinology, 2024)
In mammals, gonadal somatic cell lineage differentiation determines the development of the bipotential gonad into either the ovary or testis. Sertoli cells, the only somatic cells in the spermatogenic tubules, support spermatogenesis during gonadal development. During embryonic Sertoli cell lineage differentiation, relevant genes, including WT1, GATA4, SRY, SOX9, AMH, PTGDS, SF1, and DMRT1, are expressed at specific times and in specific locations to ensure the correct differentiation of the embryo toward the male phenotype. The dysregulated development of Sertoli cells leads to gonadal malformations and male fertility disorders. Nevertheless, the molecular pathways underlying the embryonic origin of Sertoli cells remain elusive. By reviewing recent advances in research on embryonic Sertoli cell genesis and its key regulators, this review provides novel insights into sex determination in male mammals as well as the molecular mechanisms underlying the genealogical differentiation of Sertoli cells in the male reproductive ridge.